Inhibitory Effects of Indomethacin in Human MNNG/HOS Osteosarcoma Cell Line In Vitro. (2nd January 2020) - Mirshahidi, Saied; de Necochea-Campion, Rosalia; Moretta, Annie; Williams, Nadine L.; Reeves, Mark E.; Otoukesh, Salman; Mirshahidi, Hamid R.; Khosrowpour, Shahrzad; Duerksen-Hughes, Penelope; Zuckerman, Lee M.
Abstract: Recurrence or metastasis remains the major cause of poor prognosis and mortality in Osteosarcoma patients. Therefore, development of more effective therapeutic approaches is required. We showed that indomethacin, significantly induces apoptosis in MNNG/HOS cell line, which was confirmed by morphological changes, increased Annexin-V + cells and nuclear fragmentation. Apoptosis was accompanied by increased cleavage of caspase-3 and PARP, suggesting activation of caspase-dependent cell death. Indomethacin significantly decreased the expression of β-catenin, a key player in tumor metastasis. These results indicate that indomethacin may have the potential to be used as neoadjuvant or adjuvant treatment; however, additional studies are required.